P225 Dissecting the sense of agency by targeted low-frequency rTMS. Issue 3 (March 2017) - Popa, T.; Hunt, R.; Pasternack, N.; Hallett, M.; Meunier, S.
Abstract : Introduction: Voluntary actions are characterized by a feeling that the self is the cause of action (sense of agency, SoA). SoA is created from efferent indicators (action prediction, body scheme) and afferent indicators (visual feedback, proprioception). In case of congruency between indicators, experience of SoA develops; in case of incongruence, the action is experienced as strange and non-self. Several areas have been identified by meta-analyses (Syfnozik et al., 2008; Sperduti et al, 2011 ) as potentially important for the generation of SoA. Objectives: Here we tested to what extent the pre-supplementary motor area (pSMA) and the right and left angular gyri (RAG, LAG) are involved in the SoA as assessed by "temporal binding" (TB1) (Haggard et al., 2002 ). Patients and methods: Nineteen healthy, right-handed volunteers were enrolled, and randomly distributed in 3 groups of 10 subjects each. Each group had to estimate the time delay between a movement and a subsequent sound in a test battery before and after 20 min of 1 Hz rTMS (targeting 1 area/group). The test battery consisted of 2 conditions: (VOL) the movement was a self-paced wrist extension and (EXP) the movement was a passive extension of the wrist, pulled up by the experimenter. Each movement triggered a sound via an accelerometer taped to the moving hand. Unknown to the subject, each movement-sound delay was randomly chosen delay of 100, 400, 700, or 1000 ms; however, the subjects were instructed to give their best guess on a continuous time-scale. The rTMS was applied over one of the 3 areas of interest under individualized MRI-guided neuronavigation for 1200 pulses at 110% resting motor threshold. Results: At baseline, we found TB at shorter delays, i.e., delays were estimated ∼50 ms shorter in VOL than in EXP for 100 and 400 ms. TB was eliminated by rTMS of pSMA. Conclusion: Pre-SMA and LAG are involved in agency, but in different ways: pSMA when incongruence between indicators is maximal and LAG when congruence is maximal. It might be that pSMA is more involved in SoA perception, while LAG is more related to SoA buid-up by matching the feedforward and feedback.